Thermoluminescence and structural characterization of crystalline alkali strontium borates - Nabil El-Faramawy; E.M. Abou Hussein; Mohamed El-Kinawy (Nuclear Engineering and Technology, 2025)
A strontium borate glass system was prepared by the melt-quenching method and the corresponding glass ceramic derivatives were produced by applying heat treatment (HT) on glass samples at 600 °C for different periods. FTIR analysis was carried out for the prepared and thermally treated samples. The specific volume (Vs) displayed a slight increase with HT while the oxygen packing density (OPD) revealed a slight decrease, correlating with the nature of host former, inserted modifier and rate of thermal process. The thermoluminescence (TL) properties, namely, dose response linearity, reusability, minimum detectable dose, and thermal fading, of the samples treated for 8 h were investigated. The kinetic parameters of the TL glow peaks were determined using computational and experimental methods. The dependence of the displayed glow curves/peaks on the TL measurement heating rate was investigated and quantified.